INTEGRASI NILAI-NILAI KEAGAMAAN DALAM PEMBELAJARAN SAINS DI SEKOLAH DASAR - Rosyada, Tria Amrina; Hidayah, Ery Anisfatun; Rahmawati, Risqiana (Islamic Studies Journal for Social Transformation, 2024)
This study discusses the integration of religious values into science learning in elementary schools as a strategic step to overcome the dichotomy between religious and general knowledge within Indonesia's education system. The purpose of this study is to describe the concept of integration, develop appropriate learning strategies, and analyze the potential and challenges in its implementation. This research employs a library research method by examining various sources of literature, including scientific journals, books, and official educational documents. The findings indicate that integrating religious values into science learning not only enhances students’ understanding of scientific concepts but also strengthens their spiritual and moral awareness. Strategies that can be applied include thematic integrated approaches, the use of religious-contextual learning media, setting integrated learning objectives, active learning methods, and interdisciplinary collaboration. Despite challenges such as differing approaches between religion and science, differing focus areas, and the influence of globalization, integration remains essential in shaping students who are not only knowledgeable but also possess strong character and values. Therefore, this study is expected to provide both theoretical and practical contributions for teachers, curriculum developers, and educational policymakers.